Filoctetes de Sófocles: o espaço e o labor humano - Santos, Fernando Brandão dos [UNESP] (My University, 2010)
This article analyses the transformations of spatial references in Sophocles’Philoctetes. As we can see, instead of being cristalized in formulas and conventions, Ancient Greek Theater has renewed itself constantly, by experiencing different ways to correlate audience and events on stage.

Estudo das tranformações das referências espaciais na peça Filoctetes, de Sófocles, demonstrando como o teatro grego,longe de se cristalizar em fórmulas e convenções, renova-se constantemente, experimentando diversos modos de correlacionar a audiência ao eventos apresentados em cena
Keywords: Space; Performance; Philoctetes; Sophocles; Espaço; Performance; Filoctetes; Sófocles